Sulfur reduces the root-to-shoot translocation of arsenic and cadmium by regulating their vacuolar sequestration in wheat (Triticum aestivum L.) - Shi, Gaoling; Liu, Huan; Zhou, Dongmei; Zhou, Huimin; Fan, Guangping; Chen, Wei; Li, Jiangye; Lou, Laiqing; Gao, Yan (Frontiers in Plant Science, 2022)
Accumulation of arsenic (As) and cadmium (Cd) in wheat grain is a serious threat to human health. Sulfur (S) can simultaneously decrease wheat grain As and Cd concentrations by decreasing their translocation in wheat; however, the mechanisms are unclear. We conducted hydroponic experiments to explore the mechanisms by which S modulates As and Cd translocation and their toxicity in wheat. Wheat seedlings were grown in deficient sulfate (2.5 µM) or sufficient sulfate (1.0 mM) nutrient solutions for 6 days and then exposed to zero (control), low As+Cd (1 µM As plus 0.5 µM Cd), or high As+Cd (50 µM As plus 30 µM Cd) for another 6 days. Compared with the control, plant growth was not affected by low As+Cd, but was significantly inhibited by high As+Cd. In the low As+Cd treatment, S supply had no significant effect on plant growth or root-to-shoot As and Cd translocation. In the high As+Cd treatment, sufficient S supply significantly alleviated As and Cd toxicity and their translocation by increasing phytochelatin (PC) synthesis and the subsequent vacuolar sequestration of As and Cd in roots, when compared with deficient S supply. The use of L buthionine sulfoximine (a specific inhibitor of γ-glutamylcysteine synthetase) confirmed the findings that the alleviation of As and Cd translocation and toxicity in wheat by S is mediated by increased PC production. Also, TaHMA3 gene expression in wheat root was not affected by the As+Cd and S treatments, but the expression of TaABCC1 was upregulated by the high As+Cd treatment and further increased by sufficient S supply and high As+Cd treatment. These results indicate that S-induced As and Cd subcellular changes affect As and Cd translocation mainly by regulating thiol metabolism and ABCC1 expression in wheat under As and Cd stress.